Итоги и перспективы развития технологии микроволнового нагрева диэлектрических материалов - Демьянчук, Б.А.; Оленев, Н.В. (Технология и конструирование в электронной аппаратуре, 2003)
Обсуждается физическая сущность проблем технологии традиционного микроволнового нагрева сплошных и кусочно-однородных сред с диэлектрическими потерями. Обобщены недостатки традиционных резонансных камер нагрева, вызываемые "стоячей" волной в их объеме, уходами спектра их собственных частот и протеканием поверхностных токов по стенкам камеры. В качестве перспективной альтернативы предложен нагрев в новой микроволновой нерезонансной камере, не имеющей недостатков традиционной. Отмечены возможности развития ранее не встречавшихся технологий. The physical essence of problems of technology of traditional microwave heating of continuous and partial single-row environments with dielectric losses is discussed. Deficiencies of traditional heating chambers of resonant types which are caused by: "stagnant" wave in their volume, drift of spectrum of their own frequencies and course of superficial currents on the chamber walls are generalized. It resultes in over- and underheatings of products, therefore demands sparing modes of heating. Meanwhile microwave technologies of heating lose the basic advantage over the usual thermal ones, which is fast heating in volume keeping the product quality. Heating in the new microwave none-resonant chamber, which in spite of traditional ones does not have deficiencies, is proposed as a perspective alternative. New opportunities of development of technologies not existing before are figured out on the basis of intensive, short-term, volumetric and flexibly controlled uniform heating which takes place in the mode of "running" wave. In particular, realization of selective economic and dosed heating of components of non-uniform environments, fast foaming of granuled polymeric materials, reception of volumetric plasma formations, etc. is possible.